Education Press as a Source of Reflecting the Issue on Information Security of Children in the USA - Alina Paukova (Pedagogical Discourse, 2013)
Nowadays the problem of children information safety is very actual among scholars, teachers and parents all over the world. Modern educational periodicals in the USA are analyzed as the source of showing the problem of children information safety. Author gives the classification of American educational periodicals by the type, the audience which it is intended for, the place of distribution and nature of the information. List of current issues which are devoted to the problem of children information safety are given: «Journal of Information Literacy» (JIL), «The Journal of Media Literacy», «American School Board Journal», «Net Family News», «Communications in Information Literacy». Five educational journals are analyzed in this article. The author describes the history of journals, its focus and scope, sections policies, publication frequency, access policy, archiving, conditions of subscription and key authors. Main headings of the articles concern the problem of children information safety are marked out. Laws and acts of American government that regulate the safety of American children in cyberspace are defined in the article. Author shows the main aspects of the problem of children information safety: the risks and dangers of different types of social media for children and formation the information literacy of personality. Synonyms of the term «information literacy» are given in this article. Author determines the future directions and aspects of the development of the studied problem.